تعدد الزوجات عند المسلمين في الصين وتحدياته في ظل نظام الزواج الأحادي في الصين : دراسة فقهية تحليلية - لي، بين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to study the issue of polygamy among Muslims in China and its challenges in light of the monogamy system in China. It is well known that China implements the monogamy system and as such polygamy is forbidden not only for being contrary to the purposes of monogamy, but for violating the social customs and traditions too, because most people in China are influenced by the thoughts of the feudal marriage system in feudal China which is committed to the monogamy system that permits multiple concubines. This phenomenon leads to the oppression of women and has tremendously affected their dignity and those involved in such a practice deprive the women from their rights. This humiliation serves as a means of only satisfying man's bestiality lust and that is a sign of failure and symbol of decadence. On the other hand, some Muslims in China have been practising polygamy unlawfully based on their specific circumstances despite the illegality of such a practice, thus there are juristic and legal problems as a consequences of these practices, and in addition to that, currently, in China, there has emerged serious problems during the application of the monogamy system. Thus, this research is an attempt to propose a solution to the problems arising from monogamy in China.